2019
DOI: 10.1017/sjp.2019.2
|View full text |Cite
|
Sign up to set email alerts
|

Psychological Detachment from Work during Nonwork Time and Employee Well-Being: The Role of Leader’s Detachment

Abstract: Research has shown that psychological detachment from work during nonwork time is an important recovery experience and is crucial for employee well-being. Integrating research on job-stress recovery with research on leadership and employee mental health and well-being, this study examines how a leader's psychological detachment from work during nonwork time directly relates to subordinate psychological detachment from work and indirectly to employee exhaustion and need for recovery. Based on self-report data f… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
19
0
1

Year Published

2019
2019
2023
2023

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 35 publications
(21 citation statements)
references
References 36 publications
(63 reference statements)
1
19
0
1
Order By: Relevance
“…Burnout is best predicted by combining affective rumination, negative work reflection, and psychological detachment. These findings qualify and extend the bivariate association between detachment [6,40,41] and affective rumination [23,24,25], and problem-solving pondering [42] with exhaustion found in prior research. Whereas Vandevala et al [42] found that detachment adds little to predict exhaustion beyond affective rumination, we found that detachment explains at least a modest portion of additional variance in burnout beyond affective rumination.…”
Section: Discussionsupporting
confidence: 82%
See 1 more Smart Citation
“…Burnout is best predicted by combining affective rumination, negative work reflection, and psychological detachment. These findings qualify and extend the bivariate association between detachment [6,40,41] and affective rumination [23,24,25], and problem-solving pondering [42] with exhaustion found in prior research. Whereas Vandevala et al [42] found that detachment adds little to predict exhaustion beyond affective rumination, we found that detachment explains at least a modest portion of additional variance in burnout beyond affective rumination.…”
Section: Discussionsupporting
confidence: 82%
“…Meta-analytic evidence suggests that psychological detachment will yield a negative association with exhaustion [6]. For instance, a recent study found a moderate negative association between detachment and exhaustion [40], see also the work by the authors of [41]. Furthermore, from the literature reviewed above, we expect that particularly affective rumination will yield a strong positive association to exhaustion due to its affective focus [23,24,25].…”
Section: Introductionmentioning
confidence: 99%
“…Role blurring activities include sending and receiving work‐related communications outside of normal work hours, multitasking on work and home tasks at the same time, and thinking about job‐related matters outside of regular work time (Schieman & Glavin, 2016). These actions represent ways that work can encroach on nonwork time and impair detachment and recovery from the chronic pressures of the job (Sonnentag & Schiffner, 2019; Voydanoff, 2005a). A conceptually distinct but empirically related construct—work‐to‐family conflict—refers to the process whereby the work role detracts from the finite time, energy, and attention available for the family role (Greenhaus & Beutell, 1985).…”
Section: Introductionmentioning
confidence: 99%
“…Although there are undoubtedly contextual factors that help explain these results; work-related health problems represent a transnational and transcultural problem (Bakker & Demerouti, 2013;Carod-Artal & Vázquez-Cabrera, 2012). For this reason, in recent years, researchers from different latitudes started to show interest in the processes of recovery from work-related fatigue and stress, which occur during leisure time, as well as its effects on health, wellbeing and performance at work (Fritz, Yankelevic, Zarubin, & Barger, 2010;Moreno-Jiménez & Gálvez-Herrer, 2013, Sonnentag & Schiffner, 2019.…”
Section: Introductionmentioning
confidence: 99%